Folate in health and disease - Bailey, Lynn B. , 1948- (Taylor & Francis, 2010)
Keeping up with the explosion in information garnered from fresh research, this title provides a resource on various areas of clinical interest related to folate metabolism such as: the role of folate in birth defects, cancer, cardiovascular disease, and neural tube defects. It includes estimates of dietary folate intake for the US population.